Development of a TPACK-Based PjBL Learning Model (Technological, Pedagogical, Content Knowledge) to Improve 21st Century Skills - Dewi Hanifah; Widiyanto; Ita Nuryana (Journal of Economic Education, 2026)
The development of 21st-century skills can be achieved through the learning process, one of which is through the subject of economics. The reality at SMA Negeri 1 Ambarawa shows that learning economics, especially on the material of compiling basic accounting equations, faces various challenges. First, learning tends to be teacher-centered and emphasizes memorization of concepts, is still dominated by lecture and memorization methods, and the use of technology in the learning process is still limited. The study used a quantitative approach with the development research method and the 4D development model. The resulting product is a teaching module with a TPACK-based PjBL learning model that aims to improve 21st-century skills in the material of compiling basic accounting equations. The validation results from material experts obtained scores of 3.71 and 3.62 in the feasible category and the value from media experts was 3.16 in the feasible category. The practicality test result was 3.16, which means the developed teaching module is practical to use. The N-Gain test obtained a score of 0.71, which means there is an increase in 21st-century skills using the TPACK-based PjBL learning model. The conclusion obtained is that this research produces a TPACK-based PjBL teaching module to improve 21st century skills that are effective and suitable for use in learning activities.